Uterine Cancer Treatment: Experience in two Centres in Nepal - Isha Shrestha; Binod Aryal; Saujanya Karmacharya; Neer Shobha Chitrakar; Arun Prasad Joshi; Rima Maharjan; Pabitra Maharjan; Samir Neupane; Srijana Koirala; Pratit Pokharel; Simit Sapkota; Subhas Pandit; et al. (Journal of Karnali Academy of Health Sciences, 2020)
Background: Information and studies regarding uterine cancer are limited in Nepal. The aim of this study is to assess the clinical characteristic features and treatment outcomes of uterine cancer managed in two hospitals of Nepal.